STRATEGI KOLABORASI MODEL PENILAIAN KREDIT ALTERNATIF DIGITAL PADA LEMBAGA KEUANGAN MIKRO - Hendratmoko (Jurnal Manajemen, 2022)
Microfinance Institution (MFI) is a type of financial institutions with its considerable potential to be developed, especially established to provide services in financing products for the micro and ultra-micro segments. However, many of the MFIs actually experience difficulties in evaluating the feasibility of prospective debtors due to the absence of loan history. In addition, at the aggregate level, MFIs have a high level of non-performing loans, considering that the management only relies on social relations and closeness with prospective debtors when conducting feasibility study for loan. On the other hand, a program has been initiated by OJK since 2021 in collaboration between Financial Service Institutions and Digital Financial Providers, one of which is for MFIs with the aim of increasing productivity and efficiency by digitizing business processes. Taking into consideration to the program that has been initiated by OJK and the challenges faced by MFI industry, the aim of this study is to develop a digital alternative credit scoring strategy design with a partnership scheme in microfinance institutions. In this study, several relevant theories were used to support the analysis process, including product development strategies, external analysis (PESTEL), and internal analysis (tangible and intangible resources). As for data collection techniques Included in-depth interview and document review. The results showed that the strategy is needed in the short term (less than 1 year), medium term (1-3 years), and long term (more than 3 years) starting from matching relevant services, preparing various provisions and supporting tools needed, to institutional strengthening from the MFIs that will make an optimal collaboration to increase the role and contribution of MFIs to the economic growth in the long run.